Analisis Komparatif Pengungkapan Sustainability Report Pada Perusahaan Sektor Kecantikan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2022 - Erinda Salma Imani; Dewa Ayu Chittanirmala Mahadharma; Awalita Ariyani Sujarno; Maria Yovita R Pandin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The purpose of this study is to provide empirical evidence on the disclosure of sustainability reports of beauty companies listed on the Indonesia Stock Exchange in 2022. Companies should not only think about profit, but also have social and environmental responsibilities. Sustainability Report is increasingly becoming a trend and a necessity for progressive companies to inform their stakeholders about their economic, social, and environmental performance. This study examines PT Mustika Ratu, PT Akasha Wira International, and PT Kino Indonesia, and the variable used is the level of compliance with sustainability reports. The annual reports of the companies, taken directly from the websites of the companies that are the object of the study, are the secondary data sources used in this study. The author uses the GRI index as an indicator in the implementation of sustainability reports and uses content analysis and comparative methods as analytical tools. The results showed that the three companies fall into a good category in the implementation of sustainability reports in 2022. PT Mustika Ratu, PT Akasha Wira International, and PT Kino Indonesia still have insufficient disclosure of specific economic, environmental, and social topics, mostly partially applied and limited disclosure.